Motivation and Work Engagement of the Millennials in the Workplace: Youkang Company Experience (International Journal of Applied Research in Management and Economics, 2022)
Organizations today are increasingly having a bigger proportion of millennial employees as part of their workforce. To be among others, millennial employees are competitive, civic-minded, open-minded on diversity, and achievement-oriented. They seek challenge, growth, and development; a fun work life and work-life balance. Like other generations, millennial employees need to be managed and motivated towards higher levels of performance and productivity. This research aimed to determine the relationship between the level of motivation and the level of work engagement of the employees of Youkang Company. This study used a descriptive correlational survey to collect data, with 79 millennials in the Youkang company as participants. In addition, the researcher conducted informal interviews with millennials in the Youkng company. Weighted mean, T-test and Pearson's test are some of the statistics techniques employed. Through general findings of the study, more opportunities for interaction, design more training activities, develop a reward and recognition program, regularly provide positive feedback, continuously improve the work environment and considering the model of motivation and work engagement in designing future employee programs are recommended.